Comparison of perceived family state and functioning among individuals with depression and general population in Southern Thailand - Jarurin Pitanupong; Kwanpond Traivaranon; Napakkawat Buathong (PLoS ONE, 2025)
Purpose This study aimed to examine perceived family functioning among individuals with depression, then compare these perceptions with those of the general population. Materials and methods A cross-sectional study was conducted among individuals with depression at Songklanagarind Hospital and individuals from the general population; from May to July 2024. Participants completed three questionnaires: 1) Personal and demographic inquiry, 2) the Family State and Functioning Assessment Scale (FSFAS-25), and 3) the Patient Health Questionnaire (PHQ-9). Data analysis involved descriptive statistics, Chi-square or Fisher’s exact test, Wilcoxon rank sum test and Student’s t-test. Results The study compared 41 individuals with depression with 41 from the general population; revealing significant differences in family functioning scores. The depression group reported lower median family functioning scores (76 [IQR 64-84]) compared with the general population (87 [IQR 77-93]). Fewer individuals in the depression group reported high total family functioning scores (56.1% vs. 82.9%, p = 0.016). They also showed lower percentages in family support (61.0% vs. 95.1%, p < 0.001) and discipline dimensions (46.3% vs. 78.0%, p = 0.006). Furthermore, those with residual depression symptoms (PHQ-9 having a score of nine or higher) showed significant differences in family support (37.5% vs. 76.0%, p = 0.033) and emotional status (18.8% vs. 60.0%, p = 0.023) compared with those without residual depression symptoms. Conclusion Individuals with depression demonstrated lower levels of family functioning compared with the general population. Acknowledging and addressing the influence of family dynamics on the development and persistence of the disorder may be essential for improving treatment outcomes. Integrating these factors into person-centered mental health interventions can lead to more comprehensive, individualized, and effective care.